Estrategias para la detección temprana de cáncer de ovario - Landin Pulla, Joselyn Michelle (Machala : Universidad Técnica de Machala, 2024)
Introduction: Ovarian cancer has been characterized as the gynecological neoplasm with the worst prognosis, being three times more lethal than breast cancer. Objective: to describe strategies for early detection of ovarian cancer. Methodology: A literature search was performed in specialized databases such as PubMed, Scielo and Web of Science, using keywords related to ovarian cancer, diagnosis, biomarkers and imaging techniques. Studies published since 2019 in Spanish and English language were included. Development: the high mortality of this type of cancer is due to asymptomatic tumor growth; symptoms, usually nonspecific, usually occur in advanced stages, the most common being: back pain, fatigue, abdominal pain/distension, constipation or urinary symptoms occurring at least 3 months before diagnosis. Conclusion: based on the information gathered, it is established that one of the methods of early detection of ovarian cancer are methods based on molecular biology, screening in high-risk population including adequate anamnesis, transvaginal ultrasound. Recommendation: Although there are currently cancer treatment options, the aim is to strengthen primary prevention, early diagnosis and access to health services through good diagnosis, screening and complementary tests.
Introducción: El cáncer de ovario se ha caracterizado por ser la neoplasia ginecológica de peor pronóstico, siendo tres veces más letal que el cáncer de mama.Objetivo: describir estrategias para la detección temprana de cáncer de ovario. Metodología: Se realizó una búsqueda de literatura en bases de datos especializadas como PubMed, Scielo y Web of Science, utilizando palabras clave relacionadas con el cáncer de ovario, diagnóstico, biomarcadores y técnicas de imagen. Se incluyeron estudios publicados desde el año 2019 en idioma español e inglés. Desarrollo: La alta mortalidad de este tipo de cáncer se debe a un crecimiento asintomático del tumor; los síntomas, usualmente inespecíficos, suelen presentarse en etapas avanzadas, siendo los más comunes: dolor de espalda, fatiga, dolor/distensión abdominal, constipación o síntomas urinarios que se presentan al menos 3 meses antes del diagnóstico. Conclusión: en base a la información recopilada se establece que el uno de los métodos de detección temprana de cáncer de ovario son métodos basados en biología molecular, screening en población de alto riesgo donde incluya anamnesis adecuado, ecografía transvaginal. Recomendación: A pesar de que actualmente existen opciones de tratamiento de cáncer se busca fortalecer la prevención primaria, el diagnóstico temprano y el acceso a los servicios de salud, mediante un buen diagnóstico, tamizaje y pruebas complementarias.
Keywords: CANCER DE OVARIO; SCREENING; DETECCION TEMPRANA